ANALISIS KETERAMPILAN GEOMETRI SISWA SMP IT QURROTA A’YUN PALU BERDASARKAN TINGKAT BERPIKIR VAN HILE: Analysis of Geometric Skills of Students at SMP IT Qurrota A'yun Palu Based on van Hiele's Levels of Thinking - Romu, Siti Nur Janah T.H.; Pathuddin, Pathuddin; Sukayasa, Sukayasa; Murdiana, I Nyoman (Universitas Tadulako, 2024)
This study is a qualitative research aimed at describing the geometry skills of students at SMP IT Qurrota A’yun Palu based on van Hiele's levels of geometric thinking. The subjects of this study consisted of two students with geometric thinking abilities at level 0 (visualization) and level 1 (analysis) according to van Hiele. The data in this study were obtained through written tests, interviews, and observations. The results of this study indicate that (1) students with level 0 (visualization) geometric thinking skills were able to meet two out of four visual skills indicators, two out of six verbal skills indicators, two out of four drawing skills indicators, two out of four logical skills indicators, and all four applied skills indicators. (2) Students with level 1 (analysis) geometric thinking skills were able to meet two out of four visual skills indicators, three out of six verbal skills indicators, four out of four drawing skills indicators, three out of four logical skills indicators, and all four applied skills indicators.